THE FUNDAMENTALS OF THE PROBLEMS OF AXIOLOGICAL LINGUISTICS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In recent years, concepts related to axiology began to appear in linguistics. The science of values as a term "Axiology" was introduced to the science in the second half of the 20th century by J. Gartman and P. Lapi. This term is composed of the Greek concepts "axio" (value) and "logos" (teaching), and is also called the science of values or "value science" [1; p. 19].